Politik Agraria dan Resistensi Lokal: Peran Kelompok Keagamaan dalam Penolakan Proyek Geothermal Padarincang - Lestari, Agisthia (Universitas Muhammadiyah Sorong, 2025)
This article analyses the dynamics of agrarian politics in the conflict surrounding the development of a geothermal power plant in Padarincang, Serang Regency, Banten. Although the geothermal project is positioned as part of the national Energy Transition and Sustainable Development agenda, local communities reject its presence because they consider it a threat to water sources, ecosystems, and the social and spiritual order of the community. This study uses a qualitative approach with a case study method, through in-depth interviews, observation, and documentation studies. The analysis was conducted using a critical agrarian political framework and an institutional-cultural approach. The results show that the resistance of the Padarincang community is not solely driven by economic or ecological interests, but also by moral and spiritual values. Two religious groups, namely Syarekat Perjuangan Rakyat Padarincang (SAPAR) and Gerakan Perempuan SAPAR (GRAPAS), acted as cultural political actors who articulated their rejection of the geothermal project through religious symbols, ecological ethics, and local wisdom. Religion serves as cultural and symbolic capital, strengthening social solidarity, building alternative public spaces, and providing moral legitimacy to resistance movements. This study emphasises that contemporary agrarian politics in Indonesia cannot be separated from the cultural and spiritual dimensions of local communities, and highlights the importance of a just and participatory approach to energy transition.